(378) introductory remarks on regional planning ملاحظات تمهيدية حول التخطيط الإقليمي - H.Linnomann (معهد التخطيط القومي, 2026)
ملخص في التخطيط الإقليمي، يُعرَّف الإقليم بأنه جزء محدد من أراضي الدولة يتميز بخصائص اقتصادية واجتماعية فريدة. ويمكن تمييز الأقاليم بحسب النشاط الاقتصادي الرئيسي، كالأقاليم الزراعية أو الصناعية أو التعدينية. عند تقسيم الدولة إلى أقاليم، من الضروري وجود جهة واحدة مسؤولة عن تنمية كل إقليم. في حالة جمهورية أرمينيا المتحدة، قد يكون تنظيم التخطيط الإقليمي على أساس المحافظات خيارًا مطروحًا، مع العلم أن الحدود الإدارية قد لا تتوافق مع الحدود الاجتماعية والاقتصادية المثلى. يُعد التخطيط الإقليمي أساسيًا لضمان تنمية متوازنة، وينبغي تحديد الأهداف من منظور المصلحة الوطنية. In regional planning, a region is defined as a specific part of a country's national territory with distinct economic and social characteristics. Regions can be distinguished by the primary economic activity, such as agricultural, industrial, or mining regions. When dividing a country into regions, it is crucial to have a single authority responsible for the region’s development. In the case of the U.A.R., organizing regional planning based on governorates may be an option, although administrative boundaries might not align with ideal socio-economic boundaries. Regional planning is essential to ensure balanced development, and objectives should be set from the national interest's perspective.